NEOWISE-R Caught the Luminous SN 2023ixf in Messier 101 - Schuyler D. Van Dyk; Tamás Szalai; Roc M. Cutri; J. Davy Kirkpatrick; Carl J. Grillmair; Sergio B. Fajardo-Acosta; Joseph R. Masiero; Amy K. Mainzer; Christopher R. Gelino; József Vinkó; András Péter Joó; András Pál; et al. (The Astrophysical Journal)
During routine survey imaging, the reactivated Near-Earth Object Wide-field Infrared Survey Explorer (NEOWISE-R) serendipitously caught the Type II supernova SN 2023ixf in Messier 101 on the rise, starting day 3.6 through day 10.9, and again on the decline at late times from days 211 through 213 and days 370 through 372. We have considered these mid-IR data together with observations from the ultraviolet (UV) through the near-IR, when possible. At day 3.6 we approximated the optical emission with a hot, ∼26,630 K blackbody, with a notable UV excess inferred to result from strong supernova (SN) shock interaction with circumstellar matter (CSM). In the IR, however, a clear excess is also obvious, and we fit it with a cooler, ∼1620 K blackbody with a radius of ∼2.6 × 10 ^15 cm, consistent with dust in the progenitor’s circumstellar shell likely heated by the UV emission from the CSM interaction. On day 10.8, the light detected was consistent with SN ejecta-dominated emission. At late times we also observed a clear NEOWISE-R excess, which could arise either from newly formed dust in the inner ejecta or in the contact discontinuity between the forward and reverse shocks, or from more distant pre-existing dust grains in the SN environment. Furthermore, the large 4.6 μ m excess at late times can also be explained by the emergence of the carbon monoxide 1–0 vibrational band. SN 2023ixf is the best-observed SN II in the mid-IR during the first several days after the explosion and one of the most luminous such SNe ever seen.